Research in technology and second language education developments and directions - Zhao, Yong, 1965- (Research in second language learning., 2005)
Zhao (Michigan State U.) presents a collection of 17 articles reporting on empirical studies on the effective use of computer-assisted language learning (CALL). Written by 27 academics and researchers, all but one from the U.S., the majority of the articles were previously published in scholarly journals and books.